Scope of oversight by constitutional courts over tax legislation - abdul hadi hammed hatayhat, Assist. Lect . Ali (Basra studies journal, 2022)
In every state there must be a constitution that is superior to the rest of the other legislation in the state. And, this constitution includes the general rules for regulating power, rights and freedoms that are often stipulated in the constitution. The constitution often provides this protection for its rules, by stipulating the existence of a supreme judicial authority represented by the Constitutional Court entrusted with protecting constitutional legitimacy and addressing any violation that the constitution may be subjected to. It is exposed to a violation or aggression against its constitutional rule. This is why we find that the constitutional courts have a great role in protecting the constitution, as well as interpreting its rules and drawing a work map for the ordinary legislator so that he does not fall into the same mistake in case he violates the constitutional controls